Taxation in the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2026)
The tax system constitutes one of the principal sources of public revenue for financing the State Treasury, particularly in light of the substantial financial resources required to support economic development. The fundamental challenge facing developing and least-developed countries lies in establishing a productive economic structure capable of efficiently utilizing available resources, which represents the cornerstone of sustainable economic development. Consequently, the tax system must be designed to support national development policies by encouraging investment in its various forms through the provision of tax incentives and exemptions, while simultaneously protecting domestic industries through the imposition of appropriate customs duties on imported foreign products .Furthermore, the tax system serves as a fundamental legal and economic instrument of state intervention, directing both domestic and foreign investment toward the achievement of its economic and social objectives. It also plays a significant role in addressing macroeconomic challenges, including economic recession and inflation, through the application of diverse tax policies. In addition, taxation contributes to mitigating social crises, such as housing and income distribution, by adopting fiscal measures that include increasing the minimum wage threshold exempt from taxation .Given the pivotal role of taxation in promoting economic development and achieving fiscal sustainability, it is essential to undertake a comprehensive examination of this system. This study begins by defining the concept of taxation, its significance, and its distinguishing characteristics. It then examines the tax system in the Kingdom of Saudi Arabia, focusing on its principal types and its contribution to sustainable development within the framework of Saudi Vision 2030Keywords
Keywords: Taxes; Importance of Taxes; Types of Taxes; Sustainable Development